Repercussões das guerras civis na Colômbia no sistema de ensino público, século 19 - Pico, Roger Pita (Cadernos de História da Educação, 2022)
The purpose of this article is to examine the impact of nineteenth-century civil wars on schools and colleges in Colombia through the destruction of classrooms and the occupation of troops, political repression and the military recruitment of students and teachers, and, likewise, to deepen the analysis of the repercussions on the interruption of school work and on the pace of learning, in addition to the marked fluctuations in coverage levels. The intention is to fill a historiographic void since the few studies on education in Colombia in the 19th century have focused on demonstrating the advances of this sector in times of peace. More than describing the ravages of war, this work has also recorded the efforts and sacrifices to keep educational services active even in the midst of political turmoil and military confrontation. In this sense, it is worth highlighting the initiative to help some teachers, the contribution of some public employees, the mobilization of the clergy at the parish level and the joint efforts of the different instances of the national, provincial and local government with a view to securing some resources in middle of the state of widespread devastation.